Chronic aortiс dissection: pathomorphological characteristics. - Kuzyk, Yu. I.; Sira, O. O. (Морфологія / Morphologia / Morfologìâ, 2018)
Background. Chronic aortic dissection (CAD) is a poorly understood vascular pathology. Etiology, pathogenesis, pathomorphological and clinical changes are not fully elucidated. The presence of open questions in their morphogenesis and pathomorphological picture creates difficulties in clinical diagnosis and gives rise to discussions in the choice of treatment. Objective – determinate pathomorphological changes of CAD. Methods. The analysis of 31 cases of surgical material for patients undergoing surgery on CAD was conducted. Among the operatives men dominated – 22 (70.9%), women were nine (29.1%). The age of patients ranged from 47 to 59 years. Aortic preparations were painted hematoxylin-eosin, resorcinol-fuchin for Chart, picrofuscin for Weigert, trichrome Mason. Results. The cavity of the dissection looked like a two-channel, located on the verge of adventitia and mediums, filled with blood convections, with the spread of hemorrhagic infiltration to periadventicial fatty tissue. The new pseudo-channel in one third of cases contained blood convection and fresh thrombi, and the old one was completely covered with endothelium with neointimal formation. In the media were detected massive elastolysis with contours of hyperchromic elastic fibers with signs of hyperlastosis, multiple thin layers of connective tissue fibers located between randomly scattered smooth muscle cells and collagen fibers, deeper definitions of massive enlargement of connective tissue. Conclusions. In the pathomorphological study of CAD, connective tissue remodeling of the aorta in the form of randomly located immature mesenchymal cells in combination with muscular and connective tissue transformation was revealed. The processes of vascular remodeling can provide the relative clinical stability of HRAA.